The Evaluation of a Domestic Abuse Response Team Program in an Emergency Department - Kurbatfinski, Stefan (Journal of family violence, 2024)
PurposeDomestic abuse (e.g., family violence) occurs globally and increases the risk for lifelong adverse health outcomes for all members involved. Although victims of domestic abuse often refrain from seeking support due to various reasons (e.g., fear), health centers such as emergency departments (EDs) can serve as outlets for assistance. The Domestic Abuse Response Team (DART) is a program working collaboratively with a regional hospital center in Alberta, Canada, uniquely providing immediate, expert, and patient-oriented services (e.g., safety plans) to domestic abuse victims within the ED. This study aimed to evaluate the DART program by: (1) using administrative data to characterize ED and DART patient characteristics and (2) examining staff perceptions about DART’s operations, effectiveness, challenges, and improvements.MethodsA mixed-methods approach was used to collect data from April 1st, 2019 to March 31st, 2020. Quantitative data consisted of descriptive statistics on patient and staff characteristics and qualitative data was collected through two surveys to determine perceptions of the DART program.ResultsApproximately 60% of ED patients were screened for domestic abuse and 1% were referred to DART, of which 86% were female. All referrals received support within an hour and were provided patient-oriented assistance. Qualitative data revealed that the DART program offers important support to patient victims, increases comfort around dealing with domestic abuse, and decreases ED staff workloads.ConclusionsThe DART program offers valuable support to domestic abuse victims. Staff reported that DART is effective in providing victims with immediate care and services while also supporting ED staff.